Communism and Folklore Revisited: Russian Traditional Music and the Janus-faced Nature of Soviet Cultural Politics - Morgenstern, Ulrich (Interdisciplinary Studies in Musicology, 2022)
Since the late Soviet period, ethnomusicologists and folklorists from Russia and other parts of the former Soviet Union (Izaly Zemtsovsky, Boris Putilov, Alma Kunanbaeva, Elena Razu- movskaia, Aleksandr Romodin) opened critical debates of the impact of the totalitarian system both on traditional expressive culture and on scope, theory, and method of its academic study. In the focus of these debates were a) repression against certain traditional genres and performance situations, b) imposition of arranged forms of staged performance, considerably differing from the traditional repertoire, and c) restriction, manipulation, and international isolation of scholarship. It is inherent to any totalitarianism that it demands not only obedience but also active support of a specific worldview through cultural practices. Consequently, totalitarian cultural politics include repressive as well as pedagogical aspects. Their impact on traditional music is therefore both repressive and in some (often unpredictable) ways productive. While no historically informed observer could have reason to abandon the anti-totalitarian im- petus of late 20th century Russian ethnomusicologists, I would like to offer some additions to a too simplified understanding of Soviet cultural politics impact on traditional culture. My main arguments are the following: 1. Repressive measures against traditional expressive culture, as well as the promotion of newly arranged folk music, often with a political motivation, are not a prerogative of Soviet cultural politics. 2. Stage performance in the framework of Soviet amateur art could include not only arranged folk music but also traditional forms. 3. Sometimes, Soviet reality provided new perspectives for a dynamic development of traditional expressive culture.